MicroRNA analysis of the invasive margin of glioblastoma reveals drugable therapeutic targets in lipid metabolism pathways - Alfardus, Huda (2020)
Glioblastoma (GBM) is the most common type of adult brain tumour, representing 45.2% of all malignant brain and central nervous system tumours. It is also the most lethal, with a median post-therapy survival of 14 months, due to the high likelihood of tumour recurrence. Intratumour heterogeneity is thought to be a key contributor to GBM tumour recurrence, because treatments such as radiotherapy and chemotherapy typically only successfully target the core of the tumour. Due to its high visibility, this core is excised during surgery, but there is another more subtle region of the tumour, the invasive margin, which generally remains behind. This invasive margin is a mixture between normal brain and highly invasive tumour cells. If left over from surgery, these remaining tumour cells infiltrate the normal brain, and cause recurrence within 2cm of the original site. However, if surgeons are too vigorous in removing the invasive margin, they may cause unnecessary removal of healthy brain tissue, thereby causing other complications. This make developing specific methods to target the cancer cells in the invasive margin a priority area in GBM research.